2015
DOI: 10.1371/journal.ppat.1004734
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Neutrophil, Macrophage and Dendritic Cell Responses to Yersinia pestis Transmitted by Fleas

Abstract: Yersinia pestis, the causative agent of plague, is typically transmitted by the bite of an infected flea. Many aspects of mammalian innate immune response early after Y. pestis infection remain poorly understood. A previous study by our lab showed that neutrophils are the most prominent cell type recruited to the injection site after intradermal needle inoculation of Y. pestis, suggesting that neutrophil interactions with Y. pestis may be important in bubonic plague pathogenesis. In the present study, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
3
49
0
2
Order By: Relevance
“…Intravital imaging of immune cell responses following intradermal [19] or flea-transmitted [20] Y. pestis infection in mice reveal neutrophils as the predominant cell population associated with the bacteria. However, depletion of neutrophils using an anti-GR1 antibody does not appear to alter dissemination of Y. pestis in an intradermal mouse model of infection [19], nor does depletion of neutrophils using a Ly6G antibody alter bacterial colonization during pneumonic plague [21].…”
Section: Early Interactions Of Yersinia With Host Cells-important Formentioning
confidence: 99%
“…Intravital imaging of immune cell responses following intradermal [19] or flea-transmitted [20] Y. pestis infection in mice reveal neutrophils as the predominant cell population associated with the bacteria. However, depletion of neutrophils using an anti-GR1 antibody does not appear to alter dissemination of Y. pestis in an intradermal mouse model of infection [19], nor does depletion of neutrophils using a Ly6G antibody alter bacterial colonization during pneumonic plague [21].…”
Section: Early Interactions Of Yersinia With Host Cells-important Formentioning
confidence: 99%
“…Y. pestis is detected in the dLN minutes after ID inoculation [4, 12]. Phagocytes reach LNs in hours, not minutes.…”
Section: Figurementioning
confidence: 99%
“…More recently, several groups have begun to focus on the interaction between the bacteria and specific host cell types. It has been shown that the bacteria can survive and replicate in both macrophages and neutrophils (7,8) and that they can disseminate to the draining lymph node nearest the site of flea bite within an hour (9). However, relatively few studies have investigated host factors and responses that may confer resistance to infection.…”
mentioning
confidence: 99%